Effects of Hygiene and Defecation Behavior on Helminths and Intestinal Protozoa Infections in Taabo, Côte d’Ivoire - Schmidlin, Thomas (Public Library of Science, 2013)
BACKGROUND: More than 1 billion people are currently infected with soil-transmitted helminths and schistosomes. The global strategy to control helminthiases is the regular administration of anthelmintic drugs to at-risk populations. However, rapid re-infection occurs in areas where hygiene, access to clean water, and sanitation are inadequate. METHODOLOGY: In July 2011, inhabitants from two villages and seven hamlets of the Taabo health demographic surveillance system in south-central Côte d’Ivoire provided stool and urine samples. Kato-Katz and ether-concentration methods were used for the diagnosis of Schistosoma mansoni, soil-transmitted helminths (Ascaris lumbricoides, Trichuris trichiura, and hookworm), and intestinal protozoa. Urine samples were subjected to a filtration method for the diagnosis of Schistosoma haematobium. A questionnaire was administered to households to obtain information on knowledge, attitude, practice, and beliefs in relation to hygiene, sanitation, and defecation behavior. Logistic regression models were employed to assess for associations between questionnaire data and parasitic infections. PRINCIPAL FINDINGS: A total of 1,894 participants had complete data records. Parasitological examinations revealed prevalences of hookworm, S. haematobium, T. trichiura, S. mansoni, and A. lumbricoides of 33.5%, 7.0%, 1.6%, 1.3% and 0.8%, respectively. Giardia intestinalis and Entamoeba histolytica/E. dispar were detected in 15.0% and 14.4% of the participants, respectively. Only one out of five households reported the presence of a latrine, and hence, open defecation was common. Logistic regression analysis revealed that age, sex, socioeconomic status, hygiene, and defecation behavior are determinants for helminths and intestinal protozoa infections. CONCLUSIONS/SIGNIFICANCE: We found that inadequate sanitation and hygiene behavior are associated with soil-transmitted helminths and intestinal protozoa infections in the Taabo area of south-central Côte d’Ivoire. Our data will serve as a benchmark to monitor the effect of community-led total sanitation and hygiene education to reduce the transmission of helminthiases and intestinal protozoa infections.